Afghanistan and the Troubled Future of Unconventional Warfare - Rothstein, Hy S.; Foreword By Seymour Heresh (Lahore Army Publishing House, 2010)
A Naval Postgraduate School professor and former career Special Forces officer looks at why the U.S. military cannot conduct unconventional warfare despite a significant effort to create and maintain such a capability. In his examination of Operation Enduring Freedom, Hy Rothstein maintains that although the operation in Afghanistan appeared to have been a masterpiece of military creativity, the United States executed its impressive display of power in a totally conventional manner - despite repeated public statements by Secretary of Defense Rumsfeld that terrorists must be fought with unconventional capabilities. Arguing that the initial phase of the war was appropriately conventional given the conventional disposition of the enemy, the author suggests that once the Taliban fell the war became increasingly unconventional, yet the U.S. response became more conventional.
Include Index, Notes and Bibliography
This book presents an authoritative overview of the current American way of war and addresses the specific causes of the "conventionalization" of U.S. Special Forces, using the war in Afghanistan as a case study. Drawing a distinction between special operations and unconventional warfare (the use of Special Forces does not automatically make the fighting unconventional), Rothstein questions the ability of U.S. forces to effectively defeat irregular threats and suggests ways to regain lost unconventional warfare capacity.
Keywords: United States -- Military Policy -- Afghan War (2001-)